THE COMPARISON OF ANTIFUNGAL EFFECT BETWEEN GARLIC EXTRACTS AND ALKALINE PEROXIDE TOWARDS CANDIDA - Noor Fathimah Zohra; Debby Saputera; Lia Yulia Budiarti (Dentino : Jurnal Kedokteran Gigi, 2017)
Background: Candida albicans is a microorganism found on denture plaque. Candida albicans canpenetration and accumulated on surface of the denture and then to infection the soft tissue that causes denturestomatitis. Denture cleanser has effectivity of anti-fungal is alkaline peroxide. Naturally denture cleansercontain of anti-fungal is garlic. Purpose: This research is to analyze inhibition effectivity of garlic extractconcentration 2,5%, 5%, 10%, 12,5%, 15%, and alkaline peroxide to Candida albicans growth on acrylic heatcured. Method: This research uses true experimental with post test only with control group design. Garlicextract concentration 2.5%, 5%, 10%, 12.5%, 15%, and alkaline peroxide. The method of this research usesdiffusion method with the measure of inhibition zone. Result: The result of the research garlic extractconcentration 2.5%, 5%, 10%, 12.5%, 15%, and alkaline peroxide to Candida albicans growth have inhibitionzone are 11.29mm, 13.25mm, 16.30mm, 18.2mm, 19.46mm, and 15.33mm. The result of normality test withSaphiro-Wilk is p>0,05, Levene’s test that results is p=0,575 (p>0,05) so the all data are normality andhomogenity. Analyze data uses One Way ANOVA that result is p=0,000 (p<0,05) are differences inhibitioneffectivity and next testing of Post Hoc Bonferroni show that significant differences between each group.Conclusion: The research is the differences inhibit effectivity of the garlic extract concentration 2,5%, 5%,10%, 12,5%, 15%, and alkaline peroxide to Candida albicans growth on acrylic heat cured. Garlic extract in10%, 12.5% and 15% have a bigger effectivity of inhibition than alkaline peroxide to Candida albicans growth.